Subchronic Inhalation Toxicity Study of n-pentane in Rats - Jong-Kyu Kim; Hae-Won Cho; Jeong-Hee Han; Sung-Bae Lee; Yong-Hyun Chung; Kyung-Taek Rim; Jeong-Sun Yang (Elsevier, 2012)
Objectives: This study was conducted in order to obtain information concerning the health hazards that may result from a 13 week inhalation exposure of n-pentane in Sprague-Dawley rats. Methods: This study was conducted in accordance with the Organization for Economic Co-operation and Development (OECD) guidelines for the testing of chemicals No. 413 'Subchronic inhalation toxicity: 90-day study (as revised in 2009)'. The rats were divided into 4 groups (10 male and 10 female rats in each group), and were exposed to 0, 340, 1,530, and 6,885 ppm n-pentane in each exposure chamber for 6 hour/day, 5 days/week, for 13 weeks. All of the rats were sacrificed at the end of the treatment period. During the test period, clinical signs, mortality, body weights, food consumption, ophthalmoscopy, locomotion activity, urinalysis, hematology, serum biochemistry, gross findings, organ weights, and histopathology were assessed. Results: During the period of testing, there were no treatment related effects on the clinical findings, body weight, food consumption, ophthalmoscopy, urinalysis, hematology, serum biochemistry, gross findings, relative organ weight, and histopathological findings. Conclusion: The no-observable-adverse-effect level (NOAEL) of n-pentane is evaluated as being more than 6,885 ppm (20.3 mg/L) in both male and female rats. n-pentane was not a classified specific target organ toxicity in the globally harmonized classification system (GHS).